Psychometric properties of the Dating Violence Questionnaire for Victimization and Perpetration (DVQ-VP) in Ecuadorian population - Andrés Ramírez; Luis Burgos-Benavides; Javier Herrero Díez; Hugo Sinchi-Sinchi; Alhena L. Alfaro-Urquiola; Venus Medina-Maldonado; Francisco Javier Rodríguez-Díaz (Psicologia: Reflexão e Crítica)
Abstract Objective The aim of this study was to evaluate the psychometric properties of the Dating Violence Questionnaire for Victimization and Perpetration (DVQ-VP) in a sample of the Ecuadorian population. Methods The study included 819 participants (47% men and 53% women), consisting of Ecuadorian adolescents and university students. An instrumental design was employed for the linguistic adaptation, reliability, and convergent (AVE), discriminant (HTMT), and structural (CFI, TLI, and RMSEA) validation of the DVQ-VP. The construct validity and internal consistency of the instrument were assessed. Construct validity was analyzed using confirmatory factor analysis (CFA), while internal consistency was evaluated using ordinal Cronbach’s alpha and McDonald’s omega coefficients. Additionally, a network analysis was conducted with the DVQ-VP items. Results The CFA results indicated that the DVQ-VP has a factorial structure consistent with the original theoretical model, with adequate fit indices (CFI > 990, TLI > 990, and RMSEA < 0.08 in both models of the DVQ-VP). The Cronbach’s alpha and McDonald’s omega values for the victimization and perpetration subscales were above .70, indicating good internal consistency. Additionally, the instrument proved to be sensitive in identifying different forms of dating violence. Conclusion The findings support that the DVQ-VP demonstrated adequate levels of validity and reliability for assessing dating violence in a sample of Ecuadorian adolescents and university students. These results suggest that, within this specific context and population, the instrument can be a useful tool for identifying patterns of victimization and perpetration in dating relationships. Its application may contribute to early detection and the development of targeted interventions to reduce intimate partner violence among young people.